2016
DOI: 10.1017/s0033291716002841
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of acute use of alcohol and the risk of suicide attempt

Abstract: Background While there are reviews reporting on the prevalence of acute use of alcohol (AUA) prior to suicide attempts, no review has used a meta-analytic approach to estimate common odds ratios (OR) of the effect of AUA on suicide attempts. We aim to report the results of the first meta-analysis of controlled epidemiological studies on acute alcohol use and suicide attempt. Methods The English language literature on Medline, PsychInfo, Google Scholar, and public-use databases was searched for original artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
162
1
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(185 citation statements)
references
References 46 publications
9
162
1
13
Order By: Relevance
“…This is an unfortunate missed opportunity considering that a recent household survey in a major South Indian city found that over 50% of people believe in the myth that 'suicide happens without warning' (Poreddi et al, 2016). Similarly, few articles recognised the link between poor mental health and drug/alcohol abuse with suicidality, both major risk factors for suicide (Armstrong et al, 2014;Borges et al, 2017;Cavanagh et al, 2003;Cottler et al, 2005;Hawton and van Heeringen, 2009;Nock et al, 2008) and something that is a challenge to address in India where mental health literacy is low and stigmatising attitudes are prominent (Armstrong et al, 2011;Hofmann-Broussard et al, 2017;Shidhaye and Kermode, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is an unfortunate missed opportunity considering that a recent household survey in a major South Indian city found that over 50% of people believe in the myth that 'suicide happens without warning' (Poreddi et al, 2016). Similarly, few articles recognised the link between poor mental health and drug/alcohol abuse with suicidality, both major risk factors for suicide (Armstrong et al, 2014;Borges et al, 2017;Cavanagh et al, 2003;Cottler et al, 2005;Hawton and van Heeringen, 2009;Nock et al, 2008) and something that is a challenge to address in India where mental health literacy is low and stigmatising attitudes are prominent (Armstrong et al, 2011;Hofmann-Broussard et al, 2017;Shidhaye and Kermode, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of alcohol use on mental health have been well established in the literature, and the acute use of alcohol increases the odds for suicide attempts, particularly in high doses [27, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…Bagge and Sher [28] developed a theoretical framework with complex causal chains for distal and proximal relations. In terms of the epidemiological definition of causality [29, 30], 2 main pathways from substance use to suicide can be distinguished (e.g., [31] specifically for alcohol, but the arguments apply to other substances as well): there is an acute impact of using substances via disinhibition, impulsiveness, and impaired judgment, and substances may also be used as a means to ease the distress associated with committing an act of suicide (e.g., [32]). Furthermore, there is a long-term effect of substance-use disorders on suicide mortality risk, as they can cause high distress often associated with a breakdown of social relations and social marginalization, and without any hope of improvement [33, 34].…”
Section: What Causes Of Death Were Associated With Increases In Premamentioning
confidence: 99%